The Implementation of Market Segmentation Strategy to Increase the Number of Customers of a Healthy Food and Beverage Product in Surabaya - Rizka Miladiah Ervianty (Universitas Airlangga, 2019)
This study aims to determine the application of marketing segmentation strategies to increase the number of customers of healthy food and beverage products. This study is conducted to analyze the phenomenon where the number of people suffering from obesity is increasing especially in urban areas in Indonesia. This phenomenon appears as one of the effects of changes in people's lifestyles today which tend to consume less healthy food and drinks which can trigger obesity in the body. The healthy food and beverage product, “X”, seeks to contribute a solution for public health problems as well as to meet the demand for food and beverage products that are healthy and practical to consume. The data of this study were obtained from a survey of respondents in Surabaya, East Java. Hence, descriptive statistical methods was applied. The results showed that the application of marketing segmentation strategies can increase the number of customers who buy healthy food and beverage products of the X brand.